2013
DOI: 10.1111/bph.12038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AQX‐1125, a small‐molecule SHIP1 activator

Abstract: BACKGROUNDThe efficacy of AQX-1125, a small-molecule SH2-containing inositol-5′-phosphatase 1 (SHIP1) activator and clinical development candidate, is investigated in rodent models of inflammation. EXPERIMENTAL APPROACHAQX-1125 was administered orally in a mouse model of passive cutaneous anaphylaxis (PCA) and a number of rodent models of respiratory inflammation including: cigarette smoke, LPS and ovalbumin (OVA)-mediated airway inflammation. SHIP1 dependency of the AQX-1125 mechanism of action was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…CCL2 deficiency is protective in the bleomycin model (Gharaee‐Kermani et al , ), and its levels are significantly elevated in the BAL fluid of IPF patients (Suga et al , ). Although CCL2 was not measured specifically in this study, AQX‐1125 has previously been shown to be able to decrease levels of CCL2 in the BAL fluid of LPS‐mediated pulmonary inflammation in rats (Stenton et al , ). Therefore, one possible mechanism by which SHIP1 activators like AQX‐1125 could limit fibrosis is by limiting the production of profibrotic mediators that drive the recruitment of leukocytes and fibrocytes.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…CCL2 deficiency is protective in the bleomycin model (Gharaee‐Kermani et al , ), and its levels are significantly elevated in the BAL fluid of IPF patients (Suga et al , ). Although CCL2 was not measured specifically in this study, AQX‐1125 has previously been shown to be able to decrease levels of CCL2 in the BAL fluid of LPS‐mediated pulmonary inflammation in rats (Stenton et al , ). Therefore, one possible mechanism by which SHIP1 activators like AQX‐1125 could limit fibrosis is by limiting the production of profibrotic mediators that drive the recruitment of leukocytes and fibrocytes.…”
Section: Discussionmentioning
confidence: 82%
“…In vitro , AQX‐1125 suppressed chemotaxis in human neutrophils and lymphocytes and reduced pro‐inflammatory cytokine release from murine splenocytes (Stenton et al , ). Across several in vivo rodent models of pulmonary inflammation, induced by LPS, ovalbumin or cigarette smoke, AQX‐1125 consistently reduced BAL leukocyte influx (Stenton et al , ). Similarly, we have now shown that AQX‐1125 is able to reduce cellular influx and neutrophil activity in bleomycin‐induced lung injury, and this resulted in improved outcomes through the fibrotic phase (up to Day 21) including a reduction in the pro‐fibrotic mediator, TGF‐β.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, SHIP1 knockout mice also exhibited mast cell hyperplasia, increased cytokine production and anaphylactic response (Haddon et al, 2009). A new small-molecule SHIP1 activator, AQX-1125, reduced cytokine production in splenocytes, inhibited the activation of mast cells and human leukocyte chemotaxis (Stenton et al, 2013b; Stenton et al, 2013a). However, the role of these phosphatases in mast cell chemotaxis remains to be determined.…”
Section: Chemotaxismentioning
confidence: 99%